Extraction of Carrageenan from Seaweed Eucheuma cottonii Using Sonication Method - Muhammad Arham Yunus; A. Miftah Alya Patrisya; Athiyah Nur Artanti; Indriantika Pagayang; Nur Ainun Aswa; Fiqry Maulana Aras (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study aimed to extract carrageenan from the red seaweed Eucheuma cottonii using potassium hydroxide (KOH) as solvent with the sonication method. Extraction was performed at 80°C for 60 minutes with a seaweed-to-solvent ratio of 1:30 (w/v) at an ultrasonic frequency of 40 kHz. The optimized extraction conditions yielded a carrageenan yield of 21.08%. Quality parameters evaluated included moisture content, ash content, viscosity, and gel strength. Moisture content (0.07%), ash content (0.37%), and viscosity (34.2 cP) all met FCC and FAO standards. However, the gel strength of 14.361 g/cm² did not meet the commercial standard.